2011
DOI: 10.1111/j.2041-210x.2011.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

When can we ignore the problem of imperfect detection in comparative studies?

Abstract: Summary1. Numbers of individuals or species are often recorded to test for variations in abundance or richness between treatments, habitat types, ecosystem management types, experimental treatments, time periods, etc. However, a difference in mean detectability among treatments is likely to lead to the erroneous conclusion that mean abundance differs among treatments. No guidelines exist to determine the maximum acceptable difference in detectability. 2. In this study, we simulated count data with imperfect de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 39 publications
0
65
0
5
Order By: Relevance
“…When the assumptions of statistical tests are violated, inflated type‐I error rates are expected (Osborne & Waters ; Archaux, Henry & Gimenez ). This has been demonstrated for many common analyses, such as modelling patterns in abundance with mark–recapture analysis (Archaux, Henry & Gimenez ) or Poison GLMs (White & Bennets ). To our knowledge, this is the first study that has evaluated the effect of common assumption violations on type‐I error rates for species richness estimators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the assumptions of statistical tests are violated, inflated type‐I error rates are expected (Osborne & Waters ; Archaux, Henry & Gimenez ). This has been demonstrated for many common analyses, such as modelling patterns in abundance with mark–recapture analysis (Archaux, Henry & Gimenez ) or Poison GLMs (White & Bennets ). To our knowledge, this is the first study that has evaluated the effect of common assumption violations on type‐I error rates for species richness estimators.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved with empirical and simulation studies as we have demonstrated here and others have demonstrated in the ecological literature (Zurell et al . ; Archaux, Henry & Gimenez ). The practice of simulating the experimental process can reveal the inference consequences of estimator performance when simple measures of bias and precision cannot.…”
Section: Discussionmentioning
confidence: 99%
“…Hangsleben, Allen & Gwinn, ; see Appendix S1 in Supporting Information for a stylised example of how variable p can impact inference about N ). Furthermore, the literature suggests that the probability of spurious conclusions about fish abundance can increase dramatically with only small variations in p (Archaux, Henry & Gimenez, ; Hangsleben et al ., ). For example, Hangsleben et al .…”
Section: Violations Of the Assumption Of Constant Detectionmentioning
confidence: 99%
“…Further, monitoring could be stratified to optimize resource allocation between independent samples (i.e., sites), and employ random (or systematic) sampling to secure an unbiased spatial coverage. Importantly, detection probability needs to be accounted for since even low differences in detection probability between site or years can induce spurious conclusions (Archaux et al 2011). It means that repetitive sampling of the same sites within a year should be the rule.…”
Section: Recommendationsmentioning
confidence: 99%